Advances in the regulation of bipyridine derivatives on two-dimensional (2D) supramolecular nanostructures. (12th August 2019) - Li, Xiaokang; Zhang, Siqi; Li, Jianqiao; Qian, Yuxin; Duan, Wubiao; Zeng, Qingdao
Abstract : In this review, we discuss a series of two-dimensional (2D) supramolecular nanostructures prepared on highly oriented pyrolytic graphite (HOPG) by STM. Abstract : Supramolecular self-assembly is an important strategy in nanotechnology and surface science, which has attracted extensive attention in the past decades. In this field, how to obtain more diverse two-dimensional structures and make them more stable has always been a huge challenge. Scanning Tunneling Microscopy (STM), with atomic resolution, is a unique technique for exploring supramolecular self-assembly. In this review, we present the latest progress in the development of two-dimensional (2D) nanostructures using bipyridine derivatives as ligands in our laboratory. Our focus is mainly on: (1) supramolecular coordination on the HOPG surfaces; (2) synergistic interactions of H-bonding; and (3) regulation of aromatic acid derivatives. It is worth noting that the addition of bipyridine provides a new idea and method for the construction of diverse two-dimensional self-assembly structures.